Tourism and climate change: socioeconomic implications, mitigation and adaptation measures - Bhattarai, Utsab (International Journal of Environment, 2015)
The relationship between tourism and changing climate has been discussed and studied for a relatively long time in tourism research. Over the past 15 years, more focused studies have begun to appear, and especially recently, the issue of adaptation and mitigation has been emphasized as an urgent research need in tourism and climate change studies. This paper is based on the review of selected articles which discuss the several forms of tourism and climate change and provide recommendations for mitigation and adaptation measures. This review paper assesses the impacts of climate change on the popular forms of tourism such as; mountain tourism, wildlife tourism, adventure tourism, sun/sand tourism; last chance tourism, and describes the extent of tourism vulnerabilities and their implications. The paper concludes that the appropriate adaptation and mitigation measures have to be followed to minimize the risk of climate change while trying to save all forms of tourism. The initiative of this article is to present an overview of the existing literature on the relationship between tourism and climate change in order to establish the current state of corporate and institutional responses within the tourism industry and to set out an agenda for future research. The currency of the review is evident given the recent surge in popular discussion on climate change and its effects on tourism, and the appearance of a broad and disparate array of studies on this topic. DOI: http://dx.doi.org/10.3126/ije.v4i2.12664 International Journal of Environment Vol.4(2) 2015: 355-373